Globalized Urban Precarity in Berlin and Abidjan Young Men and the Digital Economy. - Schilling, Hannah (Manchester University Press, 2023)
The comparative ethnography of young airtime sellers in Abidjan and delivery riders in Berlin analyses experiences of precarity for young men in the urban digital economy. It points to the relevance of symbolic capital in relational mechanisms of closure, domination and exploitation for making a living in globalised precarity.